2016
DOI: 10.1177/1524839916643705
|View full text |Cite
|
Sign up to set email alerts
|

Program Implementation Approaches to Build and Sustain Health Care Coordination for Type 2 Diabetes

Abstract: This article adds new insights into strategies promoting effective care coordination. The strategies that grantees implemented throughout the program align with ACA requirements, underscoring their relevance to the changing U.S. health care environment and the likelihood of further support for program sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The current study found that providers valued CCM as a key component of care that supports patient self-management of their chronic conditions. Sharing of electronic health data as a necessary facilitator of CCM was a consistent finding for this study and in the wider literature [ 17 , 18 , 23 , 24 ] on CCM. In contrast to this study which focused on NFF encounters in primary care, another qualitative study on care management focused the importance and the limitations of EHR in the coordination of care across practices [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The current study found that providers valued CCM as a key component of care that supports patient self-management of their chronic conditions. Sharing of electronic health data as a necessary facilitator of CCM was a consistent finding for this study and in the wider literature [ 17 , 18 , 23 , 24 ] on CCM. In contrast to this study which focused on NFF encounters in primary care, another qualitative study on care management focused the importance and the limitations of EHR in the coordination of care across practices [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study by Lewis and colleagues found that care management enhanced patient empowerment and addressed local barriers and individual needs with coordination of resources from a variety of settings [ 7 ], whereas the present results indicated that coordination of multiple programs addressing diabetes and its complications may hinder accessing the benefits of care management due to complex systems. Another qualitative study focusing on care coordination for insulin initiation in patients with diabetes explored different clinician perceptions of roles as they pertained to developing relationships with clear communication, trust, and respect [ 18 ]. Our results indicated that physicians and health system staff are often overwhelmed by the large volume of patients, but also concerned that patients feel they are receiving care from someone that they know and trust, as opposed to someone from another region of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Program success depends on the proper coordination among the implementers [14]. Recent studies highlight the importance to deeply understand the interaction patterns connecting the implementers.…”
Section: Introductionmentioning
confidence: 99%
“…Many models conceptualize patient complexity as number of diseases and calculation of complexity is not necessarily tied to care coordination processes (Boult et al, ; Huntley, Johnson, Purdy, Valderas, & Salisbury, ). Other models target users of high‐cost hospital services (LaPointe, ), focus on one disease such as diabetes (Fitzgerald et al, ), do not address social determinants, or fail to integrate physical and mental health services (Woltmann et al, ). Evaluation of these models and the way they quantify patient complexity is still in the early stages (Izumi et al, ).…”
Section: Introductionmentioning
confidence: 99%